2016
DOI: 10.1002/mnfr.201500936
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the sensitizing capacity and allergenicity of enzymatic cross‐linked arginine kinase, the crab allergen

Abstract: Enzymatic cross-linking with thermal polymerization of AK by tyrosinase and caffeic acid had high potential in mitigating IgE-binding activity and allergenicity, which were influenced by altering the molecular and immunological features of the shellfish protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 38 publications
6
55
0
Order By: Relevance
“…The reduction in the allergenicity of turbot PV via Tyr and CA are consistent with the changes in the structural properties. Structural changes might cause the modification of amino acid residues and binding epitopes, which agreed with the results reported in recent studies . Fei et al did some research on crosslinked thermal polymerized arginine kinase (AK) and analyzed the potential allergenicity.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The reduction in the allergenicity of turbot PV via Tyr and CA are consistent with the changes in the structural properties. Structural changes might cause the modification of amino acid residues and binding epitopes, which agreed with the results reported in recent studies . Fei et al did some research on crosslinked thermal polymerized arginine kinase (AK) and analyzed the potential allergenicity.…”
Section: Resultssupporting
confidence: 81%
“…Structural changes might cause the modification of amino acid residues and binding epitopes, which agreed with the results reported in recent studies. 13,25,45 Fei et al 45 did some research on crosslinked thermal polymerized arginine kinase (AK) and analyzed the potential allergenicity. According to the results of inhibition ELISA, the half inhibitory concentration of AK after crosslinking changed from 1.13 to 228.36 μg mL −1 and the binding activity of crosslinked thermal polymerized AK reduced.…”
Section: Igg Binding Analysis Of Crosslinked Pvmentioning
confidence: 99%
“…Thus, CTC and CHP preferentially induced Th1-and/or Treg-oriented immune response in vivo. Additionally, the group employed the same strategy and demonstrated that cross-linking arginine kinase from crab with horseradish peroxidase or tyrosinase also significantly reduced its allergenicity and promoted its capacity in inducing oral tolerance in mice [70]. Clinical trials regarding the safety and efficacies of these enzyme cross-linked allergens in treating crab allergy are imminent.…”
Section: Chemical Modificationmentioning
confidence: 99%
“…A large number of literatures have proved that enzymatic cross-linking can reduce the binding activity of IgE to allergens. For example, cross-linking with laccase can effectively reduce the allergenicity of casein in milk (Tantoush et al, 2011); similarly, cross-linking with tyrosinase and caffeic acid decreased the binding activity of peanut allergen (Chung, Kato, & Champagne, 2010;Fei et al, 2016); furthermore, transglutaminase treatment can significantly reduce the allergenicity of milk and wheat allergens (Łącka & Bryszewska, 2006;F. Z. Yuan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%